2009
DOI: 10.2460/javma.235.10.1188
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal infusion of clotrimazole for the treatment of nasal aspergillosis in two cats

Abstract: Little information is available on the treatment of nasal aspergillosis in cats, and the prognosis for affected animals is considered poor. The procedure for local intranasal infusion of clotrimazole in 2 cats was described here. Results and follow-up monitoring for both cats suggested that this may be a safe, effective, and durable treatment for cats with nasal aspergillosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…Although reported as a rare condition in cats, sino‐orbital aspergillosis is increasingly described in the published reports suggesting this may be an emerging disease 1–9 . Invasive mycotic infections in humans, as well as animals, can occur as either disseminated or localized forms.…”
Section: Introductionmentioning
confidence: 99%
“…Although reported as a rare condition in cats, sino‐orbital aspergillosis is increasingly described in the published reports suggesting this may be an emerging disease 1–9 . Invasive mycotic infections in humans, as well as animals, can occur as either disseminated or localized forms.…”
Section: Introductionmentioning
confidence: 99%
“…Feline upper respiratory tract aspergillosis (URTA), first described in 1982, (Wilkinson et al, 1982), is being increasingly reported (Barachetti et al, 2009;Barrs et al, 2012;Declercq et al, 2012;Furrow and Groman, 2009;Giordano et al, 2010;Kano et al, 2008;Kano et al, 2013;Karnik et al, 2009;Smith and Hoffman, 2010). Disease occurs over a wide geographic range, including Australia, the USA, the United Kingdom, mainland Europe, and Japan (Barrs et al, 2012;Barrs et al, 2013;Declercq et al, 2012;Goodall et al, 1984;Kano et al, 2013;Smith and Hoffman, 2010;Tomsa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Descriptions of computed tomography (CT) findings in cats with URTA are limited to case reports (Barachetti et al, 2009;Furrow and Groman, 2009;Giordano et al, 2010;Halenda and Reed, 1997;Hamilton et al, 2000;Kano et al, 2008;McLellan et al, 2006;Smith and Hoffman, 2010;Whitney et al, 2005), and one case series of mycotic rhinitis that included five cats with URTA but did not distinguish between SNA and SOA or identify the aetiological agents (Karnik et al, 2009). The objectives of this study were to describe the CT features of URTA, to determine whether cats with SOA have concurrent 3 | P a g e involvement of the SNC, and to determine if there was any association between CT features and the form of aspergillosis and/or infecting species.…”
Section: Introductionmentioning
confidence: 99%
“…Feline upper respiratory tract aspergillosis (URTA), which encompasses both sino-orbital aspergillosis (SOA) and sinonasal aspergillosis (SNA), is usually reported in immunocompetent cats. To date, only five of more than 60 cats with URTA have been identified as having concurrent, potentially immunosuppressive diseases including diabetes mellitus in three cats, feline immunodeficiency virus (FIV) infection in one and feline leukaemia virus (FeLV) infection in another (Goodall et al, 1984;Furrow and Groman, 2009;Malik et al, 2004;Barrs et al, 2015;Kano et al, 2015). Recent studies have also detected anti-Aspergillus spp.…”
Section: Introductionmentioning
confidence: 99%